Federal Mechanisms to Support Intervention Dissemination. Issue 149 (September 2015) - Diana, Augusto; Bennett, Nicole
Abstract: This paper examines federal mechanisms that support program developers and researchers in disseminating effective interventions for public benefit. The purpose of this paper is not to discuss the dissemination of intervention research (i.e., how to inform stakeholders about research findings), nor is it intended to discuss the research of intervention dissemination (i.e., what is the best approach to disseminate an intervention). Rather, the paper discusses the challenges specific to finding pathways to disseminate an intervention and describes federal opportunities to support intervention dissemination. Three specific mechanisms are discussed: Federal Registries of Evidence‐Based Programs, the Tiered Evidence Grant Programs, and the Small Business Innovative Research (SBIR) and the Small Technology Transfer Research (STTR) programs. The article presents some limitations associated with federal mechanisms for dissemination of effective interventions, but is intended to highlight current and future opportunities they may offer. © 2015 Wiley Periodicals, Inc.